2017
DOI: 10.1053/j.gastro.2017.03.023
|View full text |Cite
|
Sign up to set email alerts
|

Increased Expression of Cytotoxic T-Lymphocyte−Associated Protein 4 by T Cells, Induced by B7 in Sera, Reduces Adaptive Immunity in Patients With Acute Liver Failure

Abstract: Background & AimsPatients with acute liver failure (ALF) have defects in innate immune responses to microbes (immune paresis) and are susceptible to sepsis. Cytotoxic T-lymphocyte−associated protein 4 (CTLA4), which interacts with the membrane receptor B7 (also called CD80 and CD86), is a negative regulator of T-cell activation. We collected T cells from patients with ALF and investigated whether inhibitory signals down-regulate adaptive immune responses in patients with ALF.MethodsWe collected peripheral bloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 47 publications
(72 reference statements)
3
48
0
Order By: Relevance
“…In line with previous reports [5,14,18] , the proportion of circulating CD8 + T cells in cirrhotic patients was significantly diminished compared to HV (median values: 8.99% vs 19.85% respectively; p < 0.0 0 01). Furthermore, analyses of cytolytic mediators in CD8 + T cells from patients with cirrhosis showed significantly decreased perforin expression compared to HV (median values 18.05% vs 47.53%, respectively; p = 0.049) ( Fig.…”
Section: Peripheral Cd8 + T Cells From Cirrhotic Patients Display Ansupporting
confidence: 92%
See 1 more Smart Citation
“…In line with previous reports [5,14,18] , the proportion of circulating CD8 + T cells in cirrhotic patients was significantly diminished compared to HV (median values: 8.99% vs 19.85% respectively; p < 0.0 0 01). Furthermore, analyses of cytolytic mediators in CD8 + T cells from patients with cirrhosis showed significantly decreased perforin expression compared to HV (median values 18.05% vs 47.53%, respectively; p = 0.049) ( Fig.…”
Section: Peripheral Cd8 + T Cells From Cirrhotic Patients Display Ansupporting
confidence: 92%
“…Although partially explored, adaptive immune defects are important drivers of immune-paresis and susceptibility to infection in liver diseases. We and others have provided evidence that impaired antimicrobial responses in ALF and alcoholic acute hepatitis (AAH) were mediated by an altered phenotype of CD4 + and CD8 + T lymphocytes characterized by elevated levels of immune checkpoints PD-1, TIM-3 and CTLA-4 [10,14] .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that the pathogenesis of the disease is roughly classi ed into two aspects: direct damage and immune mediation [23], where cellular immune disorders may be the key to the occurrence of liver failure. In cellular immunity, T lymphocytes are the main effectors, which contain different subpopulations to complete the immune response to exert immune regulatory functions [24,25]. The occurrence of liver failure is caused by the killing effect of the cells during the process of clearing virus [3,20,26].…”
Section: Discussionmentioning
confidence: 99%
“…The data were expressed as means ± SD or medians with interquartile range. SPSS software V. 25 Table 1, among whom 84 (86.60%) had 500-2 × 10 6 IU/mL HBV-DNA levels, and 13 (13.40%) had less 500 IU/mL HBV-DNA levels. Laboratory indicators of measurements showed the levels of white blood count, serum TBIL and PTA, and serum sodium and creatinine were also indicated.…”
Section: Statistics and Analysismentioning
confidence: 99%
“…Cirrhosis progression End-stage fibrosis, ACLF antigen, has been elevated in both animals and patients with acute liver failure. 101 Furthermore, plasma exchange in the mouse model lowered levels of CD80 and CD86, which regulates CTLA4 expression. 101 Whether CTLA4 correlates with improved adaptive immunity and survival in liver disease remains to be seen.…”
Section: Hyperinflammatory Immunosuppressionmentioning
confidence: 99%